Does the Dark Triad of Personality Predict Corrupt Intention? The Mediating Role of Belief in Good Luck - Zhao, Huanhuan; Zhang, Heyun; Xu, Yan (Frontiers in Psychology, 2016)
The current study is the first attempt to examine the association between the Dark Triad of personality (i.e., Machiavellianism, narcissism, and psychopathy) and corruption through a mediator – belief in good luck. Based on Ajzen’s theory of planned behavior, we assumed that individuals with Dark Triad would be more likely to engage in corruption as a result of belief in good luck. In Study 1, a set of hypothetical scenarios was used to assess the bribe-offering intention and the corresponding belief in good luck. Results indicated that while the Dark Triad of personality positively predicted bribe-offering intention, it was mediated by the belief in good luck in bribe-offering. In Study 2, we presented participants with some hypothetical scenarios of bribe-taking and the corresponding belief in good luck. Findings revealed that the Dark Triad of personality was positively related to bribe-taking intention; the relationship between narcissism and bribe-taking intention, and that between psychopathy and bribe-taking intention was mediated by the belief in good luck in penalty-avoidance. However, this belief in good luck did not mediate the relationship between Machiavellianism and bribe-taking intention. These results hold while controlling for demographic variables, dispositional optimism, and self-efficacy. Taken together, this study extended previous research by providing evidence that belief in good luck may be one of the reasons explaining why people with Dark Triad are more likely to engage in corruption regardless of the potential outcomes. Theoretical and practical implications were discussed.